Isaac Foster papers - Foster, Isaac, 1740-1781.
Correspondence, legal papers relating to Foster's claims for pay, wills, and military commissions of Foster's heir, Charles H. Wainwright. Correspondence is primarily between Foster and his wife, Mary Russell Foster (also known as Polly), and contains detailed descriptions of military stations, travels, and domestic and military observations during the Revolution, 1776-1779, in which Foster served as a surgeon. Foster's letters were written mostly from near Fishkill, N. Y., and Danbury, Conn. Mary's letters, chiefly from Boston, describe domestic life and reflect the impact of war on the economy.
In part, handwritten transcripts.
Physician and military surgeon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Foster, Mary Russell -- Correspondence; Wainwright, Charles H; Boston (Mass.) -- History -- Revolution, 1775-1783.; Connecticut -- History -- Revolution, 1775-1783.; Danbury (Conn.) -- History; Fishkill (N.Y.) -- History; Massachusetts -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- History -- Revolution, 1775-1783 -- Economic aspects; United States -- History -- Revolution, 1775-1783 -- Medical care; Physicians; Surgeons